A multi-functional light-driven actuator with an integrated temperature-sensing function based on a carbon nanotube composite. Issue 12 (22nd March 2021) - Xiao, Yiwen; Lin, Jian; Xiao, Jing; Weng, Mingcen; Zhang, Wei; Zhou, Peidi; Luo, Zhiling; Chen, Luzhuo
Abstract : A multi-functional light-driven actuator is fabricated based on a carbon nanotube composite, which integrates the temperature-sensing function. Abstract : Actuators play an important role in the fields of intelligent robots and wearable electronics. Temperature has a great impact on the performances of many actuators. However, most of the traditional actuators only have an actuating function, failing to monitor and send real-time feedback of the temperature of the actuator. To solve the existing problem and break the single-function limit of traditional actuators, we propose a multi-functional light-driven actuator integrated with a temperature-sensing function, which is based on a carbon nanotube (CNT) and methylcellulose (MC) composite. When the CNT-MC film is assembled with biaxially oriented polypropylene (BOPP) to form a bilayer structure, the CNT-MC/BOPP actuator can be driven by near-infrared (NIR) light. Its morphing is based on thermal expansion differences between two layers and shrinkage of MC induced by water loss. The maximal bending curvature is up to 1.03 cm −1 . Meanwhile, the resistance of the actuator can change by about 10%, which realizes real-time temperature monitoring and feedback. Furthermore, we demonstrate two practical applications. First, the CNT-MC film can work as a temperature sensor, as its resistance changes with the temperature in real time. Second, we design an intelligent gripper, which can monitor the temperature during the entire working process. This multi-functional CNT-based device is expected to have a broad application prospect in artificial muscles, soft robotics and wearable electronics.